Fugler i Norge 2001 – Rapport fra Norsk faunakomité for fugl (NFKF) - Stokke, Bård G.; Reinsborg, Tore; Dahl, Espen Lie; Kamsvåg, Christer; Vikan, Johan R.; Rudolfsen, Geir; Solbakken, Kjetil Aa.; Størkersen, Øystein R. (Ornis Norvegica, 2006)
THE NORWEGIAN BIRD REPORT 2001 - a report on locally uncommon and scarce birds in Norway in 2001, by the Norwegian Birds Records Committee (NFKF) The basis of this report is the annual reports produced by the county rarities committees. For 2001 all the counties contributed to the report, although the Svalbard archipelago and Jan Mayen as well as Finnmark, Troms and Sogn & Fjordane counties did not produce own county reports. With the exception of the northernmost counties the report thus reflects fairly well observations from Norway in 2001. Readers should take care to note the geographical or time delimitation of the records stated for the different species, as stated in codes immediately after the scientific name of the species. The Norwegian Birds Records Committee (NFKF) has been publishing annual reports since 1991. Bewick’s Swan Cygnus columbianus numbers were the lowest since 1991, and also the occurrence of Lesser White-fronted Geese Anser erythropus at the traditional feeding and roosting site Valdakmyra, Porsanger (FI) were particularly scarce this spring (lowest since 1993). However, this could partly be explained by early arrival at the breeding sites due to unusually early snow melting. Gadwalls Anas strepera have occurred in steadily increasing numbers in Norway in recent years, and 2001 was the best year to date for this species. The number of White-billed Divers Gavia adamsii was the highest reported since 1991. This species is probably a common winter guest from Nord-Trøndelag county and northwards. Manx Shearwaters Puffinus puffinus were also recorded in good numbers in 2001, the third best year since 1991. There was a further increase in numbers at the recently established colonies of Great Cormorant Phalacrocorax carbo of the subspecies sinensis at Øra (ØF), where the first confirmed breeding was in 1997. White-tailed Eagles Haliaeetus albicilla have steadily increased in numbers and also expanded their breeding distribution southwards. Breeding is now documented in both Rogaland and Vest-Agder counties and a further expansion is expected. The Osprey Pandion haliaetus is another species that is steadily expanding its range in Norway. Avocets Recurvirostra avosetta, however, is now very unusual, with only one individual in 2001, a record low number. Several shorebirds, such as Northern Lapwings Vanellus vanellus, Great Knots Calidris canutus, Sanderlings Calidris alba, Jack Snipes Lymnocryptes minimus, Woodcocks Scolopax rusticola and Bar-tailed Godwits Limosa lapponica wintered in higher numbers than usual in 2001, probably due to winter temperatures above normal. Pomarine Skuas Stercorarius pomarinus occurred in record numbers in 2001, and also Long-tailed Skuas Stercorarius longicaudus were recorded in good numbers on migration. Furthermore, numbers of Iceland Gulls Larus glaucoides recorded were the highest since 1991, while Turtle Doves Streptopelia turtur experienced another poor year. Good numbers of Snowy Owls Bubo scandiaca were still present in 2001 after the record setting year of 2000. Kingfishers Alcedo atthis also had a good year with one breeding attempt recorded. The number of Hoopoes Upupa epops was the second best since 1991. The occurrences of Richard’s Pipits Anthus richardi, Barred Warblers Sylvia nisoria and Marsh Warblers Acrocephalus palustris were the highest ever recorded, and Red-throated Pipits Anthus cervinus showed another good year, equalling the record numbers of 2000. Blackcaps Sylvia atricapilla wintered in record numbers. Stonechats Saxicola torquata, Red-breasted Flycatchers Ficedula parva, Great Grey Shrikes Lanius excubitor and Arctic Redpolls Carduelis hornemanni all experienced second best numbers since 1991. However, traditional winter invasion species such as Pine Grosbeaks Pinicola enucleator and Two-barred Crossbills Loxia leucoptera appeared in low numbers in 2001. The Hawfinch Coccothraustes coccothraustes still shows a marked increase in the north of its distribution, especially in the Trøndelag counties, while the situation is not as bright for Ortolan Buntings Emberiza hortulana, which continues to decline in numbers and now are in danger of becoming lost as a member of the Norwegian avifauna.